Factor Structure of the Binge Eating Scale in a Large Sample of Obese and Overweight Patients Attending Low Energy Diet Therapy. (6th July 2015) - Imperatori, Claudio; Innamorati, Marco; Lamis, Dorian A.; Contardi, Anna; Continisio, Massimo; Castelnuovo, Gianluca; Manzoni, Gian Mauro; Fabbricatore, Mariantonietta
Abstract: In the present study, we evaluated the dimensionality and psychometric properties of the Italian version of the Binge Eating Scale (BES) in a 669 (127 men and 542 women) obese and overweight patients seeking weight loss treatment. All participants were administered the Italian version of the BES. Fit statistics for the alternative SEM models demonstrated that both the one‐factor and competing two‐factor models had a comparable fit to the data. Thus, we selected the one‐factor model as the most parsimonious. The BES had good internal consistency reliability (α = 0.89) with a moderate mean inter‐item correlation ( rii  = 0.34). Given that we were not able to clearly determine the best model among the competing two‐factor models and a comparable fit of these models with the one‐factor model, we have suggested that the one‐factor model is the best fitting model describing the dimensionality of the BES. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.